The Effect of Hypnobirthing Relaxation on the Anxiety Levels of Primigravida Mothers in the Third Trimester in Facing Childbirth Preparation - Lubis, Amelia (International Journal of Medicine And publich Health, 2025)
Background:Hypnobirthingis a self-hypnosis practice that aims to help expectant mothers through their pregnancy and childbirth in a natural, safe and comfortable way, overcoming fear and pain. The Hypnobirthing process is based on the power of suggestion from the mother. Women who think positively will be given suggestions and images to relax their bodies, automatically she will guide her thoughts and control her breathing. A common problem that arises in women who are about to give birth is the fear of pain or pain during the labor process. Most women who are about to give birth feel fear and anxiety. Feelings of fear and anxiety facing childbirth are not only in women who have just become pregnant, but also in women who have given birth. Purpose: This study aims to determine the Effect of Hypnobirthing Relaxation on the Anxiety Level of Third Trimester Primigravida Mothers in Facing Childbirth Preparation at BPM Lilis Suriani, 2025. Method: The type of research used is quasi-experimental research. The population in the study were all third trimester primigravida mothers at Lilis Suriani. The sampling technique used Accidental Sampling with a sample size of 20 people. Data collection with the HRS-A Hamilton Rating Scale For Anxiety instrument Data analysis used the t-test with a significant level of p <0.05). Results: The results of the analysis showed that there was an effect with a value of P = 0.001 where P = <0.05. Conclusion: It is recommended that this study can be used as information for primigravida mothers TM III at BPM Lilis Suriani to carry out Hypnobirthing either with Hypnobirthing classes or independently so that anxiety in facing childbirth can be reduced or even disappear completely.